Світовий досвід застосування алюмінієвих лігатур та передові українські розробки в цій галузі - Ліхацький, І.Ф.; Ворон, М.М.; Михалєнков, К.В. (Physico-technological Institute of Metals and Alloys, 2023)
The work is devoted to the review of master alloys, used for the preparation of aluminum alloys. It is noted that the master alloys market in the world is represented by a small number of companies that specialize in their production. It is important that large aluminum casting manufacturers, such as the German company VAW, the French Pechiney, the Norwegian corporation Norsk Hydro and others also produce or have a production base and advanced technologies for the production of master alloys of their own production and are able to meet their own demand. The classification of master alloys for aluminum alloys according to their purpose is also considered. Depending on the master alloy type, the type in which it is supplied and the features of its introduction into the melt are determined. A comparison and assessment of the state of domestic production and the master alloy market is carried out, which shows that most companies in Ukraine do not enter the market with their proposals and mainly use foreign master alloys, or small volumes of their own production. The issue of attracting innovative experience and technologies for the production of aluminum master alloys at enterprises also remains unresolved. On the example of work carried out at the Physico-technological Institute of Metals and Alloys of the NAS of Ukraine, the existing scientific and technical potential to increase the competitiveness of Ukrainian ligatures is noted. Thanks to the unique technologies and approach implemented at the Institute, it is possible to obtain master alloys of Al-Zr and Al-V systems with quality and structure indicators better than foreign analogues. Especially important is the ability to create complex and unique ligatures with a high content of modifier components at the level of 5–20 %wt. These include Al-Mo, Al-Hf, Al-Ti-Zr, Al-Fe-Mn and some others. Existing technological solutions for obtaining these and many other master alloys have a huge potential and economic feasibility not only to meet the needs of domestic industries, but also to enter the international world market.